Effectiveness of Zero Based Waste Management Policy in Realizing a Clean Gresik Regency - Hertati, Diana; Nurhadi; Tukiman (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2023)
The development of the population in an area and the existence of socio-economic activities will have an impact on increasing the type and amount of waste that will threaten the regional ecosystem. The empirical facts still reflect that waste management is not optimal with the high amount of waste entering the Ngimpik TPST, so that effective waste management is needed in realizing Gresik Regency as a clean city. This study aims to describe the Effectiveness of Waste Management based on "Zero Waste" in Creating a Clean Gresik Regency. This type of research uses a qualitative descriptive approach. Sources of data in this research include primary data and secondary data. Qualitative analysis from Miles and Huberman is used to analyze the data which includes four components, namely: data collection, data condensation, data presentation and drawing conclusions. The results of this research show that the effectiveness of the zero waste-based waste management policy at the Ngimpik TPA is quite effective. Adjustment of needs with waste management innovations that continue to be improved so that problems can be resolved. The main obstacles are the inadequate facilities and infrastructure and the lack of public awareness to reduce waste generation so that waste can be controlled, and the landfill burden will be reduced.